The Effect of Individual Hydrocarbons in the Composition of Diesel Fuel on the Effectiveness of Depressant Additives - Yana Morozova; Ilya Bogdanov; Andrey Altynov; Alina Titaeva; Maria Kirgina (Inventions, 2024)
The use of depressant additives is the most effective and cost-effective way to improve the low-temperature properties of diesel fuels, like the cloud point, cold filter plugging point and pour point. However, the effectiveness of depressant additives depends on the composition of the diesel fuel and the content of certain groups of hydrocarbons in it. In this work, the effect of adding individual hydrocarbons of various groups and structures on the effectiveness of depressant additives is studied. This study is carried out on model aromatic (toluene, tetralin) and n-paraffin hydrocarbons (cetane, heptadecane, heneicosane, docosane) in various concentrations. It is shown that the most negative effect on the depressant additives’ effectiveness is due to the content of the most polar aromatic hydrocarbons and light n-paraffins in the composition of diesel fuel, and the most positive effect is exerted by the content of heavy n-paraffins in small quantities. It is proposed to involve small concentrations (1–3% vol.) of heavy n-paraffin hydrocarbons (heneicosane, docosane) to increase the effectiveness of the depressant additive. It has been established that for the more effective action of the depressant, it is necessary to take into account the content and structure of individual hydrocarbons in the diesel fuel’s composition.